The relationship between marketing capabilities and financial performance: the moderating role of customer relationship management in Jordanian SMES - Hamzeh Alhawamdeh; Mahmoud Abdel Muhsen Irsheid Alafeef; Mohammad Abdel Mohsen Al-Afeef; Bashar Younis Alkhawaldeh; Maher Nawasra; Hani Ali Aref Al_Rawashdeh; Omar Zraqat; Lina Fuad Hussien; Ghaith N. Al-Eitan (Cogent Business & Management, 2024)
This research study addresses the complex interaction in between advertising and marketing capabilities, financial performance, and the moderating impact of consumer relationship management (CRM) in Jordanian small and medium enterprises (SMEs) in the service field. Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis was used for this study. The study clearly verifies a significant and favorable relationship in between advertising alignment and financial performance, highlighting the tactical value of customer-centric approaches. It likewise highlights the prominent function of value development in driving monetary success and the positive effect of operational capabilities on financial efficiency. Furthermore, the research study discovers the reliable moderation of CRM in the connections amongst marketing alignment, value development, operational capacities, and financial performance. These searchings for highlight the central role of CRM in improving the effect of marketing abilities on financial end results and offer useful understandings for Jordanian SMEs in the solution sector looking for to optimize financial performance and boost client connections.This research focused on investigating the impact of marketing strategies on the financial performance of Jordanian small and medium enterprises (SMEs) in the service sector. Partial Least Squares Structural Equation Modelling (PLS-SEM) was used to examine the correlations between marketing orientation, value innovation, operational capabilities and financial performance. The study found strong positive relationships between these factors and emphasised the importance of customer-centric approaches, innovation beyond products and efficient internal processes for the financial success of SMEs. The results of this study contribute to a broader discussion of SME management practises and strategies and emphasise the critical role of customer relationship management (CRM) in improving the impact of marketing, innovation and operational efficiency on financial performance. The findings of this study offer valuable insights not only for Jordanian SMEs seeking improved financial performance but also for understanding similar dynamics in SMEs around the world.
Keywords: 650; Jordanian firms; cRM; financial performance; marketing capabilities; pls-sem